PENGARUH METODE LATIHAN SINGLE LEG SPEED HOP TERHADAP KEMAMPUAN LOMPAT JANGKIT PADA PESERTA DIDIK KELAS X SMA NEGERI 2 TAPUNG HILIR M. NUR FADHOLI - M.NUR Fadholi (Universitas Syiah Kuala, 2023)
The purpose of the study. This research was motivated by the results of the triple jump carried out by the students of class X SMAN 2 Tapung Hilir not optimal and less precise in its implementation. The triple jump is an athletic sport in the form of jumping, lifting the legs up and forward in an effort to carry the point of weight as long as possible in the air.Materials and methods.. Methods This research uses an experimental method with One Group, namely Pre-test and Post-test Design. The data collection technique was saturated sampling with inclusion and exclusion criteria. Data analysis in this study used the Wilcoxon test, Paired Sample T-test.Results. Data analysis in this study used the Wilcoxon test, Paired Sample T-test. Research results based on the statistical output